2023
DOI: 10.1128/mra.01081-22
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of a Foot-and-Mouth Disease Virus Detected in Indonesia in 2022

Abstract: During 2022, outbreaks of foot-and-mouth disease (FMD) were reported across the islands of Indonesia, a country that had previously maintained an FMD-free (without vaccination) status since 1990. This report describes the near-complete genome sequence of a representative FMD virus collected from these cases belonging to the O/ME-SA/Ind-2001e lineage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…This issue leads to the importance of developing diagnostic and vaccine strategies based on the location of the virus circulated. Phylogenetic analyses of the VP1-coding region described the sequence of O/ME-SA/Ind-2001e lineage, sharing the closest nucleotide identity to other contemporary sequences collected from Indonesia [6].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…This issue leads to the importance of developing diagnostic and vaccine strategies based on the location of the virus circulated. Phylogenetic analyses of the VP1-coding region described the sequence of O/ME-SA/Ind-2001e lineage, sharing the closest nucleotide identity to other contemporary sequences collected from Indonesia [6].…”
Section: Discussionmentioning
confidence: 83%
“…FMD was reported in Indonesia in the mid-year of 2022, after IOP Publishing doi:10.1088/1755-1315/1271/1/012094 2 almost 40 years the country had not experienced an FMD outbreak. There have been reported that all the FMD cases in Indonesia are identified as FMDV type O [6].…”
Section: Introductionmentioning
confidence: 99%
“…The FMD causes a significant loss in livestock production as it causes the loss of weight, reproductive disturbances, and in the worst case, death [1]. In 2022, Indonesia had a FMD outbreak after 35 years of free cases of FMD [2]. The outbreak was first reported in East Java and then spread in other regions [3].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its indispensable role in augmenting viral replication and harbouring host's immune response, pharmaceutical agents have been designed to target 3CP [9,15]. Moreover, Indonesian serotype is very exclusive phylogenetically compared to another O serotype across Asiatic region [2]. With that uniqueness along with no information about the effect of natural compounds in inhibiting FMDV replication, particularly Indonesian serotype, underscores an avenue for exploration that could potentially enhance the arsenal against FMDV infections.…”
Section: Introductionmentioning
confidence: 99%
“…The first FMD vaccination program was an emergency response that was devoted to the dairy cattle population and government breeding centers such as the National Artificial Insemination Centre (NAIC), Singosari which was mandated to produce frozen semen in Indonesia (Zainuddin et al, 2023).…”
Section: Introductionmentioning
confidence: 99%